Bureaucracy Reform In Purworejo District Attorney - Endah Titi Wigati; Samodra Wibawa; Faizal Madya (Universitas Medan Area, 2021)
Bureaucratic reform is needed to make the government more efficient and effective. Purworejo District Attorney has implemented this bureaucratic reform since 2008. This study aims to describe the process of implementing Bureaucratic Reform at the Purworejo District Attorney in five aspects, institutional and organizational effectiveness, management, human resources, accountability and service. The method used is descriptive research with a qualitative approach. Interview data through interviews. The implementation of Bureaucratic Reform at the Purworejo District Prosecutor's Office was carried out in several stages, namely Phase I (2008-2009), Phase II (2010-2014), Phase III (2015-2019) and current conditions. Bureaucratic Reform at the Purworejo District Attorney has implemented the Integrity Zone to restore public trust, empower functional prosecutors to improve law enforcement, provide contact for public complaints, implement one stop sevices, use Information Technology to support their duties and functions. However, there are still some weaknesses, namely organizational organizations, organizations consisting of a combination of control functions and functions, responsible organization, and unsuitable employee placement.